Utilisation and Quality Management of Power Plant Fly Ash - Ambrus, Mária; Szabó, Roland; Mucsi, Gábor (International Journal of Engineering and Management Sciences, 2019)
Over the past decades, both the residential and industrial energy demand has increased due to the continuously growing consumption and production. As a large share of the electricity is still produced using fossil fuels, the utilisation of the by-products is a contemporary and pervasive issue. Fly ash is generated in large quantities in coal-fired power plants and has been proven to be an appropriate raw material for various industrial uses. Among others, it is applicable as an additive and lightweight aggregate in the cement and concrete industry, can be used for CO2 sequestration, glass foam production, catalyst production, or as a base material for geopolymers, as well. Geopolymers are inorganic polymers produced via the reaction between solid alumina and silica containing or alkali silicate materials in alkali media. Due to their numerous advantageous properties and wide variety of utilisation possibilities, research on fly ash base geopolymers became widespread topic. The quality of fly ash is determined by technical requirements, and the degree of quality control requirements depends on the final use. In certain fields of applications, standards and regulations have already been created to ensure the consistent quality of the final products made from fly ash, e.g. in the cement and concrete industry. There are various methods for fly ash processing, however, the methods to achieve the necessary properties are not standardised.